Slay - Morris, Brittney (Simon Pulse, 2019)
An honors student at Jefferson Academy and one of the only black kids there, seventeen-year-old Keira enjoys playing "Slay," a secret, multiplayer online role-playing game celebrating black culture that she secretly developed, until the two worlds collide after a Kansas City teen is murdered over a dispute in the game. Keira's previously safe space is now labeled racist, exclusionist, and violent. Now she sets out to defend her game while keeping her identity hidden.